Pastoral herding strategies and governmental management objectives: predation compensation as a risk buffering strategy in the Saami reindeer husbandry - Næss, Marius Warg; Bårdsen, Bård-Jørgen; Pedersen, Elisabeth; Tveraa, Torkild (Human Ecology, 2011)
Previously it has been found that an important risk buffering strategy in the Saami reindeer husbandry in Norway is the accumulation of large herds of reindeer as this increases long-term household viability. Nevertheless, few studies have investigated how official policies, such as economic compensation for livestock losses, can influence pastoral strategies. This study investigated the effect of received predation compensation on individual husbandry units’ future herd size. The main finding in this study is that predation compensation had a positive effect on husbandry units’ future herd size. The effect of predation compensation, however, was nonlinear in some years, indicating that predation compensation had a positive effect on future herd size only up to a certain threshold whereby adding additional predation compensation had little effect on future herd size. More importantly, the effect of predation compensation was positive after controlling for reindeer density, indicating that for a given reindeer density husbandry units receiving more predation compensation performed better (measured as the size of future herds) compared to husbandry units receiving less compensation.